Undrained shear strength of soft clay stabilised with silica fume and eggshell ASH - Ling, Sin Yie (2019)
The application of silica fume (SF) and eggshell ash (ESA) in soil stabilisation can effectively reduce the negative environmental impact, meanwhile, act as the alternative stabilisers to the costly and non eco-friendly traditional materials. This study discovers the potential of SF and in combination with ESA in stabilising the soft kaolin, in the aspects of particle size distribution (PSD), specific gravity, Atterberg limits, compaction parameters and undrained shear strength (USS). The comparison between the unstabilised soft kaolin and the stabilised kaolin with different stabilisers content is established in this study. Initially, 2 %, 4 % and 6 % SF by weight of dry soil were added to the soft kaolin and the optimum SF content was determined based on the USS. Then, 3 %, 6 % and 9 % of ESA was incorporated to the soft kaolin admixed with optimum SF content to define its ability in stabilising soft kaolin and the optimum ESA content that attributes to maximum improvement in USS. The inclusion of SF with ESA causes a considerably lower specific gravity, reduced plasticity index (PI), decreased maximum dry density (MDD), increased optimum moisture content (OMC), and higher USS than the unstabilised soft kaolin and those stabilised with SF alone. The result of unconfined compression test (UCT) reveals that the optimum stabilisers content is 6 % SF and 6 % ESA, with the greatest improvement of 68.8 % in USS. This elucidates both SF and ESA are the potential soil stabilisers.